A medical wet polyurethane foam and a method for preparing the same
Patent Information
- Application Number
- CN202611202210.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-23
AI Technical Summary
然而,该方案的B组分(水相)中水的用量仅约25份,远低于实现充分湿性发泡所需的水含量;泡沫挤出至离型纸后需在105℃高温下干燥,高温处理易破坏泡沫孔结构均匀性;且产品中引入金属粉末存在一定的生物安全性隐患
(1)优异的吸液与持续锁水性能:组合A料以高比例水(质量分数≥70%)为主体,配合多元醇类锁水剂通过多羟基氢键网络锁定水分子,使产品吸液性≥1g/cm²,吸液速度实测1.45s(标准≤8s),水分含量实测25.63%(标准≥14%),能够在伤口表面持续维持湿润微环境,湿性愈合速度较传统材料提升约2倍。
Smart Images

Figure CN122955012A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical materials technology, and in particular to a medical wet polyurethane foam and its preparation method. Background Technology
[0002] Wound dressings are essential medical materials in clinical wound care. Traditional dry dressings are mainly made of cotton gauze. During use, the gauze fibers easily adhere to the newly formed granulation tissue of the wound, requiring forced removal during dressing changes, causing secondary mechanical damage and aggravating the patient's pain. At the same time, the dry environment is not conducive to the retention of growth factors and enzymes in wound exudate, inhibiting cell proliferation and differentiation, and slowing down the healing process.
[0003] Polyurethane foam dressings have been widely studied in the field of moist wound care due to their porous, absorbent structure and good biocompatibility. A Chinese patent with authorization publication number CN 108355162 B discloses an antibacterial hydrophilic polyurethane foam medical dressing, prepared by mixing and foaming an isocyanate-terminated hydrophilic prepolymer with an aqueous phase component containing surfactants, foam stabilizers, and cationic polymer antibacterial agents. However, this design has a low water content in the aqueous phase component, lacks a dedicated softening functional component in the formulation, and still poses a certain risk of adhesion between the foam surface and newly formed tissue. Furthermore, the lack of a dedicated water-locking component makes it difficult for the foam to maintain a continuously moist microenvironment at the wound interface after absorbing exudate.
[0004] A Chinese patent with authorization announcement number CN 111001029 B discloses an antibacterial foam dressing and its preparation method. Metal powder (copper powder, silver powder, zinc powder, etc.) is added to the polyurethane material before foaming, allowing the metal powder to be embedded in the polyurethane foam material to achieve long-lasting antibacterial properties. However, the amount of water in component B (aqueous phase) of this solution is only about 25 parts, far lower than the water content required to achieve sufficient wet foaming; the foam needs to be dried at 105℃ after being extruded onto release paper, and this high-temperature treatment easily damages the uniformity of the foam pore structure; furthermore, the introduction of metal powder into the product poses certain biosafety risks.
[0005] Existing medical polyurethane foam dressing technology has at least the following shortcomings: the foam layer and the substrate film are bonded together by post-coating, resulting in insufficient bonding strength and easy delamination failure during use; the formulation system lacks a dedicated silicone softener, posing a risk of adhesion between the foam surface and newly formed granulation tissue, causing secondary mechanical damage during dressing changes; some solutions require multiple steps such as chemical grafting and hydrophilic modification, resulting in complex process routes and high production costs; existing preparation processes are mostly intermittent mold forming or release paper coating and high-temperature drying, making it difficult to achieve continuous large-scale production and resulting in poor product consistency. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a medical wet polyurethane foam and its preparation method.
[0007] The technical solution provided by this invention can, to a certain extent, overcome the deficiencies of existing wound dressings.
[0008] To achieve the above objectives, the following technical solution is adopted: The present invention provides a medical wet polyurethane foam, comprising a polyurethane film layer and a polyurethane foam layer composited on one side surface of the polyurethane film layer; the polyurethane foam layer is obtained by in-situ foaming of polyurethane prepolymer and composite material A on the surface of the polyurethane film layer, and a chemical bonding interface is formed between the polyurethane foam layer and the polyurethane film layer.
[0009] In some embodiments, component A is the core component of the medical wet polyurethane foam formulation system of the present invention, including water, polyether polyol, high-elasticity polyol, organosilicon cell opener, organosilicon softener, hydrophilic surfactant, polyol water-locking agent and antibacterial agent, and each component is formulated in a specific ratio.
[0010] In some embodiments, the polyether polyol is specifically a polyoxyethylene-polyoxypropylene copolymer polyol with a number average molecular weight of 2000-8000. One or more of the following raw materials can be selected: L-6400 (number average molecular weight of about 2900, functionality 2, EO / PO copolymer, Ningbo Wanhua or BASF, etc.), GEP-3000 (number average molecular weight of about 3000), GEP-5000 (number average molecular weight of about 5000). The polyether polyol reacts with the -NCO groups in the isocyanate prepolymer to form the soft segment skeleton of the polyurethane network, giving the foam elasticity, flexibility and mechanical strength. The polyoxyethylene segments (EO segments) are hydrophilic, which helps to improve the foam's ability to absorb aqueous permeates. The higher the molecular weight, the better the foam's softness, but the crosslinking density decreases accordingly.
[0011] In some embodiments, the high-elasticity polyol is specifically a polyoxyethylene-terminated polyether polyol with a number average molecular weight of 4000-8000; one or more of the following raw materials can be selected: EP-330NG (number average molecular weight of about 5000, primary hydroxyl content ≥75%, Ningbo Wanhua), EP-450N (number average molecular weight of about 4500), EL-450 (number average molecular weight of about 4500); the polyoxyethylene-terminated structure results in a high content of terminal primary hydroxyl groups, and the reactivity with -NCO groups is significantly higher than that of secondary hydroxyl groups, which can achieve rapid curing under conditions of lower catalyst dosage; the high molecular weight soft segments give the foam excellent compression resilience, allowing the foam to quickly return to its original shape after being compressed, improving the product's fit and cushioning protection performance; this component is functionally complementary to the aforementioned polyoxyethylene-polyoxypropylene copolyol: the former provides skeletal strength, and the latter provides high elasticity and resilience, and the two work together to construct a polyurethane foam network that combines strength and flexibility.
[0012] In some embodiments, the silicone pore-opening agent, specifically a polydimethylsiloxane-polyether copolymer silicone pore-opening agent, can be selected from one or more of the following raw materials: KF-28 (Shin-Etsu Chemical), DC-5043 (Dow Chemical), L-6900 (Momentive Specialty Chemicals), Y-10366 (Momentive Specialty Chemicals). During the foaming process, the silicone pore-opening agent migrates to the bubble wall interface, reduces the surface tension of the bubble wall, and causes the bubble wall to rupture and open under the pressure of CO2 gas, forming a connected open-cell structure. The open-cell structure is the microstructural basis for the foam to achieve vertical directional absorption of exudate, and can prevent exudate from spreading laterally inside the foam and irritating the normal skin at the edge of the wound. At the same time, the open-cell structure facilitates water vapor permeation and maintains gas exchange between the foam and the skin.
[0013] In some embodiments, the silicone softener, specifically an amino-modified polysiloxane silicone softener, may be selected from one or more of the following raw materials: L-209 (amino-modified polysiloxane, Shin-Etsu Chemical or domestic equivalent), Finish CT96E (Clariant), SM-2140 (Dow Corning / Dow Chemical), AM-300 (Shin-Etsu Chemical); the silicone softener is one of the core essential components that distinguishes this invention from the prior art. Its mechanism of action is as follows: 1. Formation of surface lubricating layer: Amino-modified polysiloxanes are oriented on the foam surface, and the PDMS main chain forms a low surface energy lubricating layer with the main chain facing outward. This significantly reduces the interfacial friction coefficient between the foam surface and the newly formed granulation tissue, giving the foam non-adhesive properties. It does not need to be forcibly removed when changing the dressing, and does not cause secondary mechanical damage; 2. Imparting a soft feel: The Si-O-Si bonds of the PDMS main chain have extremely low rotational energy barriers, giving the foam surface a soft and smooth feel; 3. Auxiliary anchoring of amino groups: Amino groups can form hydrogen bonds with urea bonds or urethane groups in the polyurethane network, so that the softener is stably bound to the foam surface and has good water washability.
[0014] The hydrophilic surfactant is a polyether-modified silicone surfactant, which is a nonionic amphiphilic surfactant with polydimethylsiloxane as the hydrophobic main chain and polyoxyethylene or polyoxyethylene-polyoxypropylene copolyether as the hydrophilic side chain, linked by Si-C bonds. The HLB value is usually 8 to 14. One or more of the following raw materials can be selected: BYK-346 (BYK Chemicals), BYK-348 (BYK Chemicals), and Silwet L-77 (Momentive Specialty Chemicals). In the preparation of component A, the polyether-modified silicone surfactant reduces the surface tension of the aqueous phase, promotes the uniform dispersion of each component (especially the silicone additives and the aqueous phase), and prevents the system from separating. In the foaming process, its amphiphilic structure stabilizes the bubble wall and regulates the uniformity of the cell size distribution. At the same time, the hydrophilic polyether segments enhance the hydrophilic wettability of the foam surface, which helps to improve the initial absorption rate of the foam to the aqueous permeate.
[0015] Polyol-based water-locking agents are small-molecule polyol compounds containing two or more hydroxyl groups (-OH), with a molecular weight not exceeding 1000; including any one or more of the following: glycerol, propylene glycol, 1,3-butanediol, sorbitol, xylitol; based on the hydrogen bond network formed between the polyhydroxyl structure and water molecules: each hydroxyl group can form hydrogen bonds (O-H…O) with 1 to 3 water molecules, and multiple hydroxyl groups work together to form a dense hydrogen bond network, "locking" water molecules inside the foam and preventing water molecules from being quickly lost due to evaporation or compression after the foam absorbs liquid.
[0016] Organic-inorganic composite antibacterial agents are composed of organic and inorganic antibacterial components. The compounding can be achieved through physical blending: the organic and inorganic antibacterial agents are weighed separately according to a certain ratio and then added to an aqueous system under stirring conditions of 40–50℃ and 300–500 rpm for uniform dispersion. The two components coexist as independent particles in the same aqueous medium to form a composite antibacterial agent. Alternatively, a carrier-based compounding method can be used. Taking zirconium phosphate as a typical carrier as an example: silver ions are introduced into the interlayer of zirconium phosphate through ion exchange, while quaternary ammonium salt organic antibacterial agents are electrostatically adsorbed using surface hydroxyl groups. This achieves the co-loading of organic and inorganic dual-effect components on the same carrier particle, forming carrier-type organic-inorganic composite antibacterial particles. The organic antibacterial components include, but are not limited to, quaternary ammonium salts. Cationic organic antibacterial agents (such as benzalkonium chloride, cetrimonium bromide, polyhexamethylene biguanide PHMB) or chlorhexidine (Hibitane) have an antibacterial mechanism through electrostatic adsorption of cationic groups onto the phospholipid bilayer of bacterial cell membranes, disrupting cell membrane integrity and leading to leakage of cell contents and cell death. Inorganic antibacterial components include, but are not limited to, silver ion inorganic antibacterial agents (such as silver-loaded zirconium phosphate, silver-loaded zeolite, and silver sulfate) or zinc ion antibacterial agents (such as zinc sulfate and zinc oxide with a particle size greater than 100 nm). Their antibacterial mechanism involves the binding of metal ions to functional groups such as thiol groups (-SH) and amino groups (-NH2) in bacterial proteins, causing protein denaturation and inactivation, while simultaneously disrupting bacterial DNA replication. Compared to traditional elemental metal powders (copper powder, silver powder, zinc powder, etc.) as antibacterial components, this reduces the risk of powder detaching from the foam and entering the bloodstream through wounds. Furthermore, the organic-inorganic composite antibacterial system, combined with a slightly acidic foaming environment (product pH 5-8, measured 6.6), achieves a sustained-release antibacterial function.
[0017] The polyurethane film layer is a crucial functional component of the medical wet polyurethane foam product of this invention. Covering the outer side of the polyurethane foam layer, it serves to provide waterproofing and breathability, protect the foam layer, and isolate external contaminants. The polyurethane film layer of this invention is self-made. By introducing hydrophilic soft segments of polyethylene glycol (PEG) and controlling the -NCO / -OH molar ratio, the film achieves a moisture permeability of not less than 4500 g / m²·24H while actively participating in the in-situ foaming interface chemical bonding reaction to form a stable covalent bond interface. Traditional films are prone to delamination failure under liquid absorption and swelling stress. This invention overcomes the shortcomings of existing technologies where the film only serves as a passive substrate and the interface bonding relies on physical adhesion.
[0018] This invention achieves an active interface through the following formulation design: First, in the polyurethane film layer formulation, the molar ratio (i.e., NCO / OH molar ratio) of diisocyanate (HDI or MDI) to all hydroxyl-containing components (—OH of PEG, PBA, BDO, and DMPA) is controlled to be slightly lower than the stoichiometric ratio, specifically controlled within the range of NCO / OH = 0.95 to 0.98. That is, hydroxyl groups (—OH) exist in excess relative to isocyanate (—NCO). During the crosslinking and curing stage, the insufficient number of —NCO groups in the system are completely consumed, and the reaction automatically terminates due to the depletion of —NCO. A large number of unreacted active hydroxyl groups remain at the ends of the polyurethane molecular chains. The residual —OH is mainly distributed at the ends of the hydrophilic soft segments of PEG. The glass transition temperature of PEG segments is much lower than -50℃, and the chain segment movement is active at foaming temperatures of 35 to 45℃. The residual —OH has sufficient activity and can react with the excess —NCO groups in the subsequently coated foam slurry to form urethane bonds.
[0019] Secondly, in the formulation, dimethylolpropionic acid (DMPA) introduces side-attached carboxyl groups (-COOH) into the film. Since the activation energy of the reaction between -COOH and -NCO is significantly higher than that between -OH and -NCO, the conversion rate of -COOH is much lower than that of -OH within a short curing window of only 3-5 minutes at 120-140℃. A large amount of -COOH remains stably on the film surface in an active form. When the subsequent foam slurry (containing excess -NCO) is foamed in situ at 35-45℃, the -NCO in the slurry reacts slowly with the residual -COOH on the film surface throughout the foaming process, forming amide bonds in situ. A small amount of CO2 is released during the reaction. 2. It is integrated into the foaming system without affecting the interface quality; at the same time, there is a surface hydrophilic segment segregation effect: during the high-temperature drying and curing process of the film, driven by the thermodynamic minimization of surface energy, PEG segments and -COOH-containing segments spontaneously undergo micro-phase separation and enrichment on the film surface (the surface in contact with air), forming a hydrophilic surface layer. This makes the density of residual active groups (-OH and -COOH) on the film surface significantly higher than that of the film bulk phase, ensuring high reactivity at the interface with the foam slurry. The above together form a stable interface between the film and the foam layer mainly based on covalent bonding. The interface peel strength is significantly better than that of the physical adhesion interface, and the product does not delamination failure under liquid absorption and swelling conditions.
[0020] The NCO / OH molar ratio mentioned above must be controlled within the range of 0.95 to 0.98: if it is below 0.95, there will be too many residual active groups, and the mechanical properties of the film will decrease; if it is above 0.98, there will be too few residual active groups, insufficient interfacial chemical bonding density, and limited improvement effect on interfacial adhesion.
[0021] The specific preparation process of the polyurethane film layer consists of the following five steps.
[0022] Step (1) Prepolymer synthesis: Polyethylene glycol (PEG, Mw 1000~4000, 30~50 parts by weight) and polybutylene adipate diol (PBA, Mw) are synthesized. 1000-3000 parts by weight (20-35 parts by weight) are added to a reactor and vacuum dehydrated at 80-90°C for 2 hours to remove residual moisture from the raw material (moisture content reduced to below 0.05 wt%), preventing moisture from reacting with -NCO groups and consuming isocyanate components. After dehydration, the temperature is lowered to 60-70°C, and HDI or MDI (25-35 parts by weight) and the catalyst dibutyltin dilaurate (DBTDL) (0.02-0.05 parts by weight) are added. Nitrogen gas is introduced for protection, and the reaction is stirred at 60-70°C for 2-3 hours. The -NCO content is measured periodically (by di-n-butylamine back titration) until the -NCO content reaches the theoretical calculated value (within ±0.2%). The reaction is then stopped to obtain a polyurethane prepolymer containing -NCO end groups. Step (2) Chain extension and solution preparation: Dissolve dimethylolpropionic acid (DMPA, 1-3 parts by weight) and 1,4-butanediol (BDO, 3-8 parts by weight) in an appropriate amount of N,N-dimethylformamide (DMF) or butanone (MEK) to prepare a chain extender solution; add the chain extender solution to the polyurethane prepolymer obtained in step (1), and continue stirring at 70-80℃ for 1-2 hours to complete the chain extension and further increase the molecular weight; after the chain extension reaction is completed, add the leveling agent polyether. A modified silicone surfactant (0.5–1 part by weight, BYK-346) was used. The solid content of the system was adjusted to 35–50 wt% with DMF or MEK. The viscosity was measured at 25°C, and the coating viscosity was controlled within the range of 3000–8000 mPa·s to obtain the polyurethane film coating solution. During the preparation process, the NCO / OH molar ratio in the final formula must be monitored and controlled to be 0.95–0.98 to ensure that sufficient residual active hydroxyl groups are retained on the film surface to achieve the active interface function. Step (3) Coating and film formation: The polyurethane film coating liquid obtained in step (2) is uniformly coated onto the silicone oil-treated PET release paper by doctor blade coating or slit extrusion coating process; the wet film thickness is controlled within the range of 80-150 μm by the doctor blade gap or slit width, corresponding to a final film thickness of 15-50 μm after drying (when the solid content is 35-50 wt%, the dry-wet film thickness ratio is about 1:3-1:4); the coating speed is controlled at 5-15 m / min to ensure coating uniformity; Step (4) Drying and curing: The PET release paper coated with the coating liquid is continuously fed into a multi-stage temperature-controlled drying tunnel; the temperature of the first drying tunnel is 60-80℃ for 8-12 minutes to evaporate most of the solvent (DMF or MEK) and allow the film to initially form; the temperature of the second drying tunnel is 120-140℃ for 3-5 minutes to further cross-link and cure the polyurethane molecular chains, forming a complete polyurethane film network, while allowing the carboxyl groups introduced by DMPA to be fully exposed on the film surface; the drying and curing process must ensure that the solvent is fully evaporated and that the residual amount of DMF in the finished film does not exceed the safety standards for medical materials. Step (5) Rewinding for later use: Cool the polyurethane film layer after drying and curing in step (4) to room temperature, and rewind it together with the PET release paper to obtain a polyurethane film layer roll for later use; when using, unfold the roll, use the polyurethane film layer (after removing the release paper) as the coating substrate, and uniformly coat the polyurethane foam slurry on the film surface according to step (3) of the preparation method of this invention, and send it into the foaming box for in-situ foaming and molding to obtain a medical wet polyurethane foam that integrates the polyurethane foam layer and the polyurethane film layer.
[0023] The performance indicators of the polyurethane film layer obtained according to the above formula and preparation process are as follows: moisture permeability is 4500~8000g / m²·24H (determined according to GB / T 12704.1 standard, cup method); film thickness is 15~50μm; tensile strength is not less than 10MPa (determined according to GB / T 1040 standard); solvent (DMF) residue meets the requirements of ISO 10993-17 standard; biocompatibility meets the requirements of GB / T 16886 series standards.
[0024] Understandably, the above solvent-based preparation process can be replaced by a solvent-free waterborne polyurethane dispersion (WPU) coating process: a hydrophilic modified waterborne polyurethane dispersion (WPU, with a solid content of 35-50 wt% and a PEG segment content of not less than 25 wt% on a solid basis, containing -COOH hydrophilic groups, and an NCO / OH molar ratio controlled at 0.95-0.98) is used to replace the solvent-based polyurethane coating liquid. After being mixed evenly with a waterborne blocked isocyanate crosslinking agent (3-6 parts by weight, Trixene BI 7982, Covestro), it is coated onto PET release paper, dried at 60-80℃ for 10-15 min to evaporate the moisture, and then crosslinked and cured at 120-140℃ for 3-5 min to obtain a polyurethane film layer.
[0025] The moisture permeability of the polyurethane film layer is not less than 4500 g / m²·24H; the water mass fraction in the composite material A is not less than 70%, and the composite material A contains both silicone softener and polyol water-locking agent; the liquid absorption of the medical wet polyurethane foam is not less than 1 g / cm², the liquid absorption rate is not more than 3s, the moisture content is not less than 14%, the density is 80-120 kg / m³, the expansion rate is not more than 35%, the pH value is 5-8, the thickness is 15-50 μm; the outer surface of the polyurethane film layer is waterproof, and the water contact angle is not less than 90°.
[0026] In some embodiments, the medical wet polyurethane foam product has a two-layer structure, consisting of, from top to bottom: a wet polyurethane foam layer 2 and a polyurethane film layer 1.
[0027] In some embodiments, the medical wet polyurethane foam product further includes a release film layer, which is peelably applied to the surface of the wet polyurethane foam layer opposite to the polyurethane film layer, for protecting the wet polyurethane foam layer before use. In this case, the product structure is a three-layer structure, as shown in the attached figure. Figure 1 As shown, from top to bottom, they are: release film 3 (upper layer), wet polyurethane foam layer 2 (middle layer), and polyurethane film layer 1 (lower layer).
[0028] The release film layer is a silicone oil-treated polyethylene terephthalate (PET) release film or polyethylene (PE) release film, with a thickness of 25-75 μm and a peel force of 5-30 g / 25mm.
[0029] This invention also provides a method for preparing medical wet polyurethane foam, comprising the following steps: Step (1): Add water, polyether polyol, high-elasticity polyol, organosilicon pore-opening agent, organosilicon softener, hydrophilic surfactant, water-locking agent, and composite antibacterial agent to a stirring container in the formula amount at 40-50℃, stir at 300-500 rpm for 8-12 minutes, and cool down to 10-13℃ after stirring evenly to obtain combination A; the mass fraction of water is not less than 70% based on the total weight of combination A; the water-locking agent is a polyol-based water-locking agent; the composite antibacterial agent is an organic antibacterial agent or an organic-inorganic composite antibacterial agent, and does not contain elemental metal powder; Step (2): The polyurethane prepolymer and the combined material A obtained in step (1) are injected into a high-speed mixer at a mass ratio of 13:10 using a metering device. The temperature of the polyurethane prepolymer is controlled at 23-25°C and the temperature of the combined material A is controlled at 10-13°C. The mixture is stirred at a speed of 4500-6500 rpm for 3-5 seconds to obtain polyurethane foam slurry. Step (3): The polyurethane foam slurry obtained in step (2) is uniformly coated onto the continuously operating polyurethane film layer, wherein the moisture permeability of the polyurethane film layer is not less than 4500g / m²·24H. Step (4): The polyurethane film layer coated with the polyurethane foam slurry is continuously fed into the foaming box and foamed in situ for 4-8 minutes at 35-45°C and normal pressure to obtain a medical wet polyurethane foam semi-finished product in which the polyurethane foam layer and the polyurethane film layer are integrated. Step (5): Cut and roll the semi-finished product obtained in step (4) as needed and then package it to obtain the finished medical wet polyurethane foam.
[0030] The beneficial effects of this invention are as follows: (1) Excellent liquid absorption and continuous water-locking performance: Combination A material is mainly composed of a high proportion of water (mass fraction ≥70%), combined with polyol water-locking agents to lock water molecules through a multi-hydroxy hydrogen bond network, so that the liquid absorption of the product is ≥1g / cm², the actual liquid absorption speed is 1.45s (standard ≤8s), and the actual moisture content is 25.63% (standard ≥14%). It can maintain a moist microenvironment on the wound surface, and the wet healing speed is about 2 times faster than traditional materials.
[0031] (2) Non-sticky and soft feel: The silicone softener (amino-modified polysiloxane) forms a low-friction lubricating layer on the foam surface, which significantly reduces the interfacial adhesion between the foam and the newly formed granulation tissue. It does not cause secondary mechanical damage when changing the dressing, and the feel is soft and comfortable. The product has a pH value of 5 to 8 (6.6 in actual measurement). The slightly acidic environment works together with the compound antibacterial agent to inhibit bacterial growth.
[0032] (3) Foam-film integrated chemical bonding interface: The present invention adopts a process of continuous in-situ foaming on a high moisture permeability polyurethane film layer. The NCO groups in the foam slurry and the surface active groups of the polyurethane film layer form a chemical covalent bonding interface in situ during the foaming process. The interface bonding force is far superior to the physical post-bonding process. The product does not delaminate under liquid absorption and expansion conditions, and the structure is stable and reliable.
[0033] (4) Continuous large-scale production capacity: The process of this invention organically connects the steps of preparing the combined A material, high-speed mixing with dual temperature difference control, continuous coating and foaming on the film, cutting, winding and packaging, etc., realizing the continuous large-scale production of medical wet polyurethane foam, with high production efficiency, good product size consistency and low overall production cost.
[0034] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and will become apparent from the description or may be learned by means of the embodiments thereof. Attached Figure Description
[0035] Figure 1This is a schematic diagram of the exploded structure of a medical wet polyurethane foam according to the present invention.
Detailed Implementation Methods
[0036] Unless otherwise specified, all raw materials used in the following examples are commercially available. The raw materials used unless otherwise specified are as follows: the polyether polyol is a polyoxyethylene-polyoxypropylene copolymer polyol with a number average molecular weight of approximately 2900 (L-6400, EO / PO copolymer, Ningbo Wanhua or BASF, etc.); the high-elasticity polyol is a polyoxyethylene-terminated polyether polyol with a number average molecular weight of approximately 5000 (EP-330NG, primary hydroxyl content ≥75%, Ningbo Wanhua); the silicone pore-opening agent is a polydimethylsiloxane-polyether copolymer (KF-28, Shin-Etsu Chemical); the silicone softener is an amino-modified polysiloxane (L-209, Shin-Etsu Chemical); the hydrophilic surfactant BYK-346 is a polyether-modified silicone surfactant; the water-locking agent glycerin is food-grade glycerin (purity ≥99.5%); and the composite antibacterial agent is a complex of a quaternary ammonium salt organic antibacterial agent and a silver ion inorganic antibacterial agent.
[0037] In the following examples, the product performance testing methods are as follows: liquid absorbency is calculated according to YY / T 1293.2 standard, in units of g / cm²; liquid absorption rate is the time required for 2 mL of simulated body fluid to be completely absorbed (in seconds); moisture content is calculated according to the formula (in %); swelling rate is calculated according to the formula (in %), and measured in both the transverse and longitudinal directions; pH value is measured after extraction at 37℃ for 2 hours; appearance is inspected visually.
[0038] Example 1 First, a polyurethane thin film layer is prepared. The specific preparation process consists of the following five steps.
[0039] Step (1) Prepolymer synthesis: Polyethylene glycol (PEG, Mw 1000~4000, 40 parts by weight) and polybutylene adipate diol (PBA, Mw 1000~3000, 25 parts by weight) were added to the reactor and vacuum dehydrated at 90°C for 2 hours to remove residual moisture from the raw materials (moisture content reduced to below 0.05wt%), preventing moisture from reacting with -NCO groups and consuming isocyanate components; after dehydration, the temperature was lowered to 70°C, MDI (35 parts by weight) and catalyst dibutyltin dilaurate DBTDL (0.02 parts by weight) were added, nitrogen gas was introduced for protection, and the reaction was stirred at 70°C for 3 hours. The -NCO content was measured periodically (by di-n-butylamine back titration) until the -NCO content reached the theoretical calculated value (within ±0.2%), and the reaction was stopped to obtain a polyurethane prepolymer containing -NCO end groups; Step (2) Chain extension and solution preparation: Dimethylolpropionic acid (DMPA, 2 parts by weight) and 1,4-butanediol (BDO, 6 parts by weight) are dissolved in an appropriate amount of N,N-dimethylformamide (DMF) to prepare a chain extender solution; the chain extender solution is added to the polyurethane prepolymer obtained in step (1), and the reaction is continued at 75°C for 2 hours to complete the chain extension and further increase the molecular weight; after the chain extension reaction is completed, leveling agent polyether modified organosilicon surfactant (0.5 parts by weight, BYK-346) is added, and the solid content of the system is adjusted to 45wt% with DMF or MEK. The viscosity is measured at 25°C, and the coating viscosity is controlled within the range of 3000~8000mPa·s to obtain the polyurethane film coating solution; during the preparation process, the NCO / OH molar ratio in the final formula must be monitored and controlled to be 0.95 to ensure that sufficient residual active hydroxyl groups are retained on the film surface to achieve the active interface function; Step (3) Coating and film formation: The polyurethane film coating liquid obtained in step (2) is uniformly coated onto the silicone oil-treated PET release paper by doctor blade coating or slit extrusion coating process; the wet film thickness is controlled at 112 μm by the doctor blade gap or slit width, corresponding to a final film thickness of 24 μm after drying (when the solid content is 42 wt%); the coating speed is controlled at 15 m / min to ensure coating uniformity; Step (4) Drying and curing: The PET release paper coated with the coating liquid is continuously fed into a multi-stage temperature-controlled drying tunnel; the temperature of the first drying tunnel is 80°C and the time is 12 minutes to evaporate most of the solvent (DMF) and allow the film to initially form; the temperature of the second drying tunnel is 140°C and the time is 5 minutes to allow the polyurethane molecular chains to further cross-link and cure, forming a complete polyurethane film layer network, while allowing the carboxyl groups introduced by DMPA to be fully exposed on the film surface; the drying and curing process must ensure that the solvent is fully evaporated and the residual amount of DMF in the finished film does not exceed the requirements of the medical material safety standard. Step (5) Rewinding for later use: Cool the polyurethane film layer after drying and curing in step (4) to room temperature, and rewind it together with the PET release paper to obtain a polyurethane film layer roll for later use; when using, unfold the roll and use the polyurethane film layer (after removing the release paper) as the coating substrate.
[0040] The performance indicators of the polyurethane film layer obtained according to the above formula and preparation process are as follows: moisture permeability is 5500 g / m²·24H (determined according to GB / T 12704.1 standard, cup method); film thickness is 25 μm; tensile strength is 12.8 MPa (determined according to GB / T 1040 standard); solvent (DMF) residue meets the requirements of ISO 10993-17 standard; biocompatibility meets the requirements of GB / T 16886 series standards.
[0041] Next, medical-grade wet polyurethane foam products are prepared: Weigh out 80.8 parts by weight of water, 8 parts by weight of polyether polyol, 4 parts by weight of high-elasticity polyol, 2 parts by weight of silicone pore opener, 1 part by weight of silicone softener, 1 part by weight of hydrophilic surfactant, 3 parts by weight of glycerin, and 0.2 parts by weight of composite antibacterial agent per 100 parts by weight, and set aside.
[0042] Add the weighed water to a mixing container and heat to 45°C. Then, sequentially add the silicone pore-opening agent, silicone softener, high-elasticity polyol, polyether polyol, hydrophilic surfactant, glycerin, and composite antibacterial agent. Stir at 400 rpm for 10 minutes until all components are uniformly dispersed. After stirring, cool the mixture to 10–13°C to obtain composite material A for later use. The water mass fraction in composite material A is approximately 80.8%.
[0043] Take TDI prepolymer (isocyanate group content NCO% 10%) and control its temperature at 25℃; maintain the temperature of the above-mentioned component A at 13℃. Using a filling machine for precise metering, inject both TDI prepolymer and component A at a mass ratio of 13:10 into a high-speed mixer simultaneously. Stir at 5500 rpm for 4 seconds to ensure thorough mixing of the TDI prepolymer and component A, forming a uniform polyurethane foam slurry. The approximately 12℃ temperature difference between the prepolymer and component A effectively reduces the initial reaction rate. Combined with ultra-high-speed stirring for precise control of CO2 foaming timing, this results in a fine and uniform bubble distribution.
[0044] The obtained polyurethane foam slurry was uniformly coated onto a continuously operating polyurethane film layer using a coating device. The polyurethane film layer had a moisture permeability of 5500 g / m²·24H and a thickness of 25 μm. The polyurethane film layer coated with polyurethane foam slurry was continuously fed into a foaming chamber and foamed in situ for 5 minutes at 40°C and normal pressure. During this process, the NCO groups in the polyurethane foam slurry reacted chemically with the active groups on the surface of the polyurethane film layer to form a chemical bonding interface, achieving integrated composite of the foam layer and the film layer. After foaming and molding, the foam was cut, rolled up, and packaged to obtain the finished medical wet polyurethane foam product.
[0045] The medical-grade wet polyurethane foam product also includes a polyethylene (PE) release film with a thickness of 30 μm. This release film layer is peelably applied to the surface of the wet polyurethane foam layer opposite to the polyurethane film layer, protecting the wet polyurethane foam layer before use. In this case, the product structure is a three-layer structure, as shown in the attached diagram. Figure 1 As shown, from top to bottom, they are: release film 3 (upper layer), wet polyurethane foam layer 2 (middle layer), and polyurethane film layer 1 (lower layer).
[0046] The obtained product underwent full performance testing according to the above testing methods. The test results are as follows: The appearance is a white roll material with fine and uniform pores and a soft feel; the density is 112.7 kg / m³ (standard 80~120 kg / m³, qualified); the liquid absorption speed is 1.45s (standard ≤8s, qualified); the liquid absorption rate is 1.209 g / cm² (standard ≥1g / cm², qualified); the moisture content is 25.63% (standard ≥14%, qualified); the transverse expansion rate is 23.93% (standard ≤35%, qualified); the longitudinal expansion rate is 28.16% (qualified); and the pH value is 6.6 (standard 5~8, qualified).
[0047] Example 2 The difference between this embodiment and Example 1 is that the TDI prepolymer is replaced with MDI prepolymer (diphenylmethane diisocyanate prepolymer, isocyanate group content NCO% is 12%), the temperature of the MDI prepolymer is controlled at 25°C, and the polyurethane film layer and the formulation and dosage of combination A material, as well as the other process parameters are exactly the same as in Example 1.
[0048] Compared to TDI prepolymer, MDI prepolymer has superior hydrolytic stability, and the resulting foam exhibits better structural stability under long-term contact with exudate, making it particularly suitable for the care of chronic wounds with large exudate volumes (such as pressure sores, diabetic foot ulcers, etc.).
[0049] The obtained product was tested for performance according to the above test methods. The results showed that the product was white roll material with fine and uniform pores and a soft feel; the density was 108.3 kg / m³ (qualified); the liquid absorption speed was 1.62 s (qualified); the liquid absorption rate was 1.185 g / cm² (qualified); the moisture content was 24.87% (qualified); the transverse expansion rate was 24.51% (qualified); the longitudinal expansion rate was 29.03% (qualified); and the pH value was 6.7 (qualified). All performance indicators met the requirements for medical wet dressings.
[0050] Example 3 This example is a formulation dosage adjustment example, used to verify the reliability of product performance when the water content in component A is at the lower limit of the dosage range. Based on 100 parts by weight, the following are weighed: 75 parts by weight of water, 10 parts by weight of polyether polyol, 6 parts by weight of high-elasticity polyol, 3 parts by weight of silicone pore-opening agent, 1.5 parts by weight of silicone softener, 1.5 parts by weight of hydrophilic surfactant, 4 parts by weight of glycerin, and 0.3 parts by weight of composite antibacterial agent.
[0051] Following the preparation process of Example 1, the above components were sequentially added to a stirring vessel at 45°C and stirred at 400 rpm for 10 minutes. The mixture was then cooled to 13°C to obtain composite material A. The water content in composite material A was approximately 75% by mass, thus maintaining the synergistic effect of the silicone softener and the glycerol water-locking agent. Subsequent polymerization and foaming steps were identical to those in Example 1, using TDI prepolymer (NCO% 12%, temperature 25°C) at a mass ratio of 13:10, stirred at 5500 rpm for 4 seconds, and foamed at 40°C under normal pressure for 5 minutes.
[0052] The performance of the obtained product was tested: It is a white roll material with uniform pores and a soft feel; its density is 115.2 kg / m³ (qualified); its liquid absorption rate is 2.08 s (qualified); its liquid absorbency is 1.046 g / cm² (qualified); its moisture content is 18.35% (qualified); its transverse swelling rate is 26.74% (qualified); its longitudinal swelling rate is 30.12% (qualified); and its pH value is 6.5 (qualified). The results show that when the water content is 75 parts by weight, all performance indicators of the product still meet the requirements for medical wet dressings, proving the rationality of the lower limit of the water content range in the claims.
[0053] Example 4 This example is a substitution example for silicone additives, used to verify the substitutability of similar silicone additives. In the formulation of component A, the silicone pore-opening agent KF-28 is replaced with DC-5043 (Dow Chemical, similar polydimethylsiloxane-polyether copolymer, 2 parts by weight), and the silicone softener L-209 is replaced with Finish CT 96E (similar amino-modified polysiloxane, 1 part by weight); the remaining components (80.8 parts water, 8 parts polyether polyol L-6400, 4 parts high-elasticity polyol EP-330NG, 1 part hydrophilic surfactant BYK-346, 3 parts glycerin, 0.2 parts composite antibacterial agent) and their amounts are the same as in Example 1. The preparation process, polymerization reaction parameters, and foaming molding process are completely the same as in Example 1.
[0054] The performance of the obtained product was tested: It was a white roll material with fine and uniform pores and a soft feel; its density was 110.5 kg / m³ (qualified); its liquid absorption rate was 1.53 s (qualified); its liquid absorption capacity was 1.197 g / cm² (qualified); its moisture content was 25.11% (qualified); its transverse expansion rate was 24.38% (qualified); its longitudinal expansion rate was 28.64% (qualified); and its pH value was 6.6 (qualified). The results show that replacing KF-28 with a similar polydimethylsiloxane-polyether copolymer and replacing L-209 with a similar amino-modified polysiloxane resulted in product performance comparable to Example 1, demonstrating the good substitutability of similar organosilicon additives.
[0055] Example 5 This example is an alternative to polyol-based water-locking agents, used to verify the scalability of polyol-based water-locking agents. In the formulation of component A, glycerol is replaced with propylene glycol (3 parts by weight); the remaining components (80.8 parts water, 8 parts polyether polyol L-6400, 4 parts high-elasticity polyol EP-330NG, 2 parts silicone pore-opening agent KF-28, 1 part silicone softener L-209, 1 part hydrophilic surfactant BYK-346, 0.2 parts composite antibacterial agent) and their amounts are the same as in Example 1. Propylene glycol also has a polyhydroxy structure and can lock water molecules through a hydrogen bond network to maintain a moist microenvironment inside the foam; its water-locking mechanism is the same as that of glycerol. The formulation process, polymerization reaction parameters, and foaming molding process are completely identical to those in Example 1.
[0056] The performance of the obtained product was tested: It was a white roll material with uniform pores and a soft feel; its density was 111.8 kg / m³ (qualified); its liquid absorption rate was 1.71 s (qualified); its liquid absorption capacity was 1.163 g / cm² (qualified); its moisture content was 21.47% (qualified); its transverse swelling rate was 25.16% (qualified); its longitudinal swelling rate was 29.38% (qualified); and its pH value was 6.5 (qualified). The results indicate that by replacing glycerol with propylene glycol as a polyol-based water-locking agent, the product's moisture content still met the requirement of ≥14%, and its water-locking function was effectively maintained.
[0057] Comparative Example 1 This comparative example is used to verify the essential contribution of silicone softener to the non-stickiness and soft feel of the product. Based on the formulation of compound A in Example 1, silicone softener L-209 was removed (the amount was set to 0), while the remaining components (80.8 parts water, 8 parts polyether polyol L-6400, 4 parts high-elasticity polyol EP-330NG, 2 parts silicone pore opener KF-28, 1 part hydrophilic surfactant BYK-346, 3 parts glycerin, and 0.2 parts composite antibacterial agent) and their amounts remained unchanged. The preparation process, polymerization reaction parameters, and foaming molding process were completely the same as in Example 1.
[0058] The obtained product underwent performance testing and adhesion evaluation: density was 113.2 kg / m³; liquid absorption rate was 1.58 s; liquid absorption was 1.198 g / cm²; moisture content was 25.41%; lateral expansion rate was 24.07%; and pH value was 6.6. Although the above physicochemical performance indicators were still within the acceptable range, the product's appearance and feel were noticeably harder, and the surface smoothness decreased. The foam obtained in Comparative Example 1 and the foam obtained in Example 1 were respectively applied to the surface of simulated new granulation tissue (simulated with gelatin gel). After contacting them at 37°C and under humid conditions for 24 hours, the peeling force required for removal was measured. The peeling force of the foam obtained in Comparative Example 1 was significantly higher than that in Example 1, and obvious tear marks appeared on the surface of the simulated tissue upon removal, while the foam obtained in Example 1 showed no adhesion or tissue damage upon removal. As can be seen from the comparison between Example 1 and Comparative Example 1, the introduction of silicone softener significantly reduces the interfacial adhesion between the foam and the newly formed tissue by forming a low-friction amino-modified polysiloxane lubricating layer on the foam surface, giving the product non-stickiness and a soft feel, and effectively avoiding secondary mechanical damage during dressing changes. This effect cannot be achieved by existing solutions that do not introduce silicone softener.
[0059] Comparative Example 2 This comparative example is used to verify the necessary contribution of polyol-based water-locking agents to maintaining a continuously moist microenvironment in foam. Based on the formulation of component A in Example 1, the glycerol water-locking agent was removed (the amount was set to 0), while the remaining components (80.8 parts water, 8 parts polyether polyol L-6400, 4 parts high-elasticity polyol EP-330NG, 2 parts silicone pore-opening agent KF-28, 1 part silicone softener L-209, 1 part hydrophilic surfactant BYK-346, and 0.2 parts composite antibacterial agent) and their amounts remained unchanged. The preparation process, polymerization reaction parameters, and foaming molding process were completely the same as in Example 1.
[0060] The resulting product underwent performance testing: density was 109.6 kg / m³; liquid absorption rate was 1.89 s; liquid absorbency was 1.021 g / cm²; moisture content was 8.74% (below the 14% standard, unqualified); lateral expansion rate was 25.32%; pH value was 6.8. A comparison between Example 1 and Comparative Example 2 shows that after removing the glycerol water-locking agent, the product's moisture content plummeted from 25.63% to 8.74%, far below the ≥14% standard requirement. The foam, after absorbing exudate, could not sustainably maintain a moist microenvironment at the wound interface, severely impairing the moist healing function. This indicates that the role of the glycerol polyhydroxy structure in locking water molecules through a hydrogen bond network is irreplaceable, and polyol water-locking agents are essential components in the formulation system of this invention for maintaining a continuously moist microenvironment.
[0061] Comparative Example 3 This comparative example is used to verify the technical advantages of continuous in-situ foaming molding process (chemical bonding interface) over post-lamination process. Polyurethane foam slurry was prepared according to the formulation and polymerization parameters of component A in Example 1, but the molding method was changed: the foam slurry was poured into a mold (the mold size corresponds to the product specifications of Example 1) and cured at 40°C for 5 minutes to obtain a polyurethane foam sheet. The above foam sheet was then laminated with a polyurethane film layer of the same specifications as in Example 1 (moisture permeability 5500 g / m²·24H, thickness 25 μm) by hot pressing at 80°C, pressure 0.3 MPa, and time 30 s, simulating the physical post-lamination process in the prior art.
[0062] The resulting product underwent performance testing and interfacial bonding evaluation: density was 114.1 kg / m³; liquid absorption rate was 2.34 s; liquid absorption capacity was 1.087 g / cm²; moisture content was 22.16%; transverse expansion rate was 27.83%; and pH value was 6.7. Although the above physicochemical performance indicators were basically qualified, after the liquid absorption performance test, when the product was removed from the liquid, obvious interfacial delamination occurred between the foam layer and the film layer under the action of liquid absorption expansion stress. The peel force test showed that the interfacial peel strength was only about 35% of that of Example 1. Comparative Example 3 also had obvious defects in continuous production: the intermittent molding method could not achieve continuous mass production, the dimensional consistency of each batch of products was poor, the production efficiency was low, and the overall production cost was significantly higher than that of the continuous in-situ foaming process of Example 1. As can be seen from the comparison between Example 1 and Comparative Example 3, the present invention adopts a continuous in-situ foaming process on a highly moisture-permeable polyurethane film layer, which enables the NCO groups in the foam layer and the surface active groups of the film to form a chemical bonding interface in situ during the foaming process. The interface bonding force is far superior to the physical bonding of the subsequent bonding process. The product does not delaminate under liquid absorption and expansion conditions, and at the same time, it realizes continuous large-scale production with good product consistency.
[0063] Test Example 1 The medical wet polyurethane foam products obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were subjected to full performance tests. The test methods were the same as described above, and the results are summarized in Table 1.
[0064] Table 1 Performance test results of each embodiment and comparative example product
[0065] As shown in Table 1, the performance indicators of the products obtained in Examples 1 to 5 all meet the requirements for medical wet dressings, proving that the technical solution of the present invention has good stability and reliability within the range of formulation components and dosages. In Comparative Example 1, the adhesiveness of the product increased significantly after removing the silicone softener; in Comparative Example 2, the moisture content decreased to 8.74% after removing the glycerin water-locking agent, failing to maintain a moist microenvironment; in Comparative Example 3, using a post-bonding process, the interfacial bonding strength was only about 35% of that in Example 1, and delamination failure occurred after liquid absorption.
[0066] Obviously, the polyurethane prepolymer is not limited to TDI prepolymer or MDI prepolymer, but can also be other isocyanate-terminated polyurethane prepolymers, but must be prepolymers that have not been chemically grafted modified, and the isocyanate group content (NCO%) is preferably 5-15% by weight. The preparation temperature of the composite material A is not limited to 45℃, and the components can be fully dissolved and mixed in the range of 40-50℃; the stirring speed is not limited to 400 rpm, and the preparation requirements can be met in the range of 300-500 rpm. Obviously, the foaming box temperature is not limited to 40℃, and atmospheric pressure in-situ foaming molding can be achieved in the range of 35-45℃; the foaming time is not limited to 5 min, and the foam can be fully cured in the range of 4-8 min; the moisture permeability of the polyurethane film is not limited to 5500 g / m²·24H, as long as the moisture permeability is not less than 4500 g / m²·24H, the requirements for gas exchange and water vapor permeation of the product can be met, and the film thickness is preferably 15-50 μm.
[0067] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A medical-grade wet polyurethane foam, characterized in that: The product includes a polyurethane film layer and a polyurethane foam layer composited on one side of the polyurethane film layer. The polyurethane foam layer is obtained by in-situ foaming of a polyurethane prepolymer and a composite material A on the surface of the polyurethane film layer. The composite material A contains water, polyether polyol, high-elasticity polyol, silicone cell opener, silicone softener, hydrophilic surfactant, polyol water-locking agent, and composite antibacterial agent.
2. The medical wet polyurethane foam according to claim 1, characterized in that: Based on the total mass of the combined material A, the mass fraction of water is not less than 70%; the moisture permeability of the polyurethane film layer is not less than 4500 g / m²·24H; and the liquid absorption of the medical wet polyurethane foam is not less than 1 g / cm².
3. The medical wet polyurethane foam according to claim 1, characterized in that: The polyurethane prepolymer is an unmodified toluene diisocyanate prepolymer or diphenylmethane diisocyanate prepolymer; the isocyanate group content of the polyurethane prepolymer is 5-15% by weight.
4. The medical wet polyurethane foam according to claim 1, characterized in that: Based on a total weight of 100 parts by weight for all components of the aforementioned Combination A, the amount of water is 75-90 parts by weight, the amount of polyether polyol is 5-12 parts by weight, the amount of high-elasticity polyol is 2-7 parts by weight, the amount of organosilicon pore-opening agent is 1-4 parts by weight, the amount of organosilicon softener is 0.5-2 parts by weight, the amount of hydrophilic surfactant is 0.5-2 parts by weight, the amount of polyol water-locking agent is 1-5 parts by weight, and the amount of composite antibacterial agent is 0.1-0.5 parts by weight.
5. The medical wet polyurethane foam according to claim 4, characterized in that: The polyether polyol is a polyoxyethylene-polyoxypropylene copolymer polyol with a number average molecular weight of 3000-8000; the high-elasticity polyol is a polyoxyethylene-terminated polyether polyol with a number average molecular weight of 4000-8000; the organosilicon pore-opening agent is a polydimethylsiloxane-polyether copolymer organosilicon pore-opening agent; the organosilicon softener is an amino-modified polysiloxane organosilicon softener; the hydrophilic surfactant is a polyether-modified organosilicon surfactant; the polyol water-locking agent is a polyol compound containing two or more hydroxyl groups and with a molecular weight not exceeding 1000; and the composite antibacterial agent is a complex of a quaternary ammonium salt organic antibacterial agent and a silver ion inorganic antibacterial agent.
6. The medical wet polyurethane foam according to claim 1, characterized in that: The density of the medical wet polyurethane foam is 100-120 kg / m³; the liquid absorption rate does not exceed 3 seconds; the moisture content is 20-30%; the transverse expansion rate does not exceed 25% and the longitudinal expansion rate does not exceed 30%.
7. The medical wet polyurethane foam according to claim 2, characterized in that: The moisture permeability of the polyurethane film layer is 4500-8000 g / m²·24H, and the thickness is 15-50 μm.
8. The medical wet polyurethane foam according to claim 1, characterized in that: It also includes a release film layer, which is peelably covered on the side of the wet polyurethane foam layer opposite to the polyurethane film layer, for protecting the wet polyurethane foam layer before use.
9. The medical wet polyurethane foam according to claim 8, characterized in that: The release film layer is a silicone oil-treated polyethylene terephthalate (PET) release film or a polyethylene (PE) release film with a thickness of 25–75 μm.
10. A method for preparing medical wet polyurethane foam, characterized in that: The preparation steps of the medical wet polyurethane foam include: Step (1): Add water, polyether polyol, high-elasticity polyol, silicone pore-opening agent, silicone softener, hydrophilic surfactant, polyol water-locking agent, and composite antibacterial agent sequentially to a mixing container at 40-50°C according to the formula amount. Stir at 300-500 rpm for 8-12 minutes. After stirring evenly, cool down to 10-13°C to obtain composite material A. The water content is not less than 70% based on the total weight of composite material A. Step (2): The polyurethane prepolymer and the combination A material obtained in step (1) are injected into a high-speed mixer according to the formula amount through a metering device. The temperature of the polyurethane prepolymer is controlled at 23-25℃ and the temperature of the combination A material is controlled at 10-13℃. The mixture is stirred at a speed of 4500-6500 rpm for 3-5 seconds to obtain polyurethane foam slurry. Step (3): The polyurethane foam slurry obtained in step (2) is uniformly coated onto the continuously operating polyurethane film layer, wherein the moisture permeability of the polyurethane film layer is not less than 4500g / m²·24H. Step (4): The polyurethane film layer coated with the polyurethane foam slurry is continuously fed into the foaming box and foamed in situ for 4-8 minutes at 35-45°C and normal pressure to obtain a medical wet polyurethane foam semi-finished product in which the polyurethane foam layer and the polyurethane film layer are integrated. Step (5): Cut and roll the semi-finished product obtained in step (4) as needed and then package it to obtain the finished medical wet polyurethane foam.
11. The preparation method according to claim 10, characterized in that: Based on a total weight of 100 parts by weight for all components of the aforementioned Combination A, the amount of water is 75-90 parts by weight, the amount of polyether polyol is 5-12 parts by weight, the amount of high-elasticity polyol is 2-7 parts by weight, the amount of organosilicon pore-opening agent is 1-4 parts by weight, the amount of organosilicon softener is 0.5-2 parts by weight, the amount of hydrophilic surfactant is 0.5-2 parts by weight, the amount of polyol water-locking agent is 1-5 parts by weight, and the amount of composite antibacterial agent is 0.1-0.5 parts by weight.
12. The preparation method according to claim 10, characterized in that: The polyurethane prepolymer is an unmodified toluene diisocyanate prepolymer or diphenylmethane diisocyanate prepolymer; the isocyanate group content of the polyurethane prepolymer is 5-15% by weight.
13. The preparation method according to claim 10, characterized in that: The polyether polyol is a polyoxyethylene-polyoxypropylene copolymer polyol with a number average molecular weight of 3000-8000; the high-elasticity polyol is a polyoxyethylene-terminated polyether polyol with a number average molecular weight of 4000-8000; the organosilicon pore-opening agent is a polydimethylsiloxane-polyether copolymer organosilicon pore-opening agent; the organosilicon softener is an amino-modified polysiloxane organosilicon softener; the hydrophilic surfactant is a polyether-modified organosilicon surfactant; the polyol water-locking agent is a polyol compound containing two or more hydroxyl groups and with a molecular weight not exceeding 1000; and the composite antibacterial agent is a complex of a quaternary ammonium salt organic antibacterial agent and a silver ion inorganic antibacterial agent.
14. The preparation method according to claim 10, characterized in that: The polyurethane film layer is prepared by the following steps: (1) Polyethylene glycol and polybutylene adipate diol are dehydrated under vacuum at 80-90°C, then cooled to 60-70°C, and hexamethylene diisocyanate or 4,4'-diphenylmethane diisocyanate and catalyst are added. The reaction is carried out under nitrogen protection for 2-3 hours to obtain polyurethane prepolymer containing -NCO end groups. (2) Add dimethylolpropionic acid and 1,4-butanediol to the prepolymer obtained in step (1), and perform chain extension reaction at 70-80°C for 1-2 hours. Add leveling agent, adjust the solid content to 35-50 wt% and viscosity to 3000-8000 mPa·s with solvent, and control the NCO / OH molar ratio to 0.95-0.98 to obtain coating liquid; (3) The coating liquid obtained in step (2) is coated onto the release paper with a wet film thickness of 80-150 μm. After drying at 60-80℃ for 8-12 min and then cross-linking and curing at 120-140℃ for 3-5 min, the paper is rolled up to obtain a polyurethane film layer.
15. Use of a medical wet polyurethane foam in the preparation of wound dressings for moist healing care of abrasions, burns, pressure ulcers or postoperative wounds, wherein the medical wet polyurethane foam is the medical wet polyurethane foam according to any one of claims 1-9.
Citation Information
Patent Citations
An antibacterial hydrophilic polyurethane foam medical dressing
CN108355162B
An antibacterial foam dressing and its preparation method
CN111001029B